PENGARUH TAI-CHI EXERCISE TERHADAP INTENSITAS NYERI RHEUMATOID ARTHRITIS PADA LANSIA - Ningsih, Ratna (Politeknik Kesehatan Kemenkes Bengkulu, 2016)
The number of elderly in Indonesia each year has increased. The problemsarises because of the elderly such physical and economic dependence, chronic diseaseswere Rheumatoid Arthritis, Hypertension, deafness. Rheumatoid Arthritis which ranksfirst (44%) suffered from chronic diseases. Profile of Bengkulu in 2012 of 27.104patients with Rheumatoid Arthritis and in 2013 as many as 26.212 people. Rejang LebongHealth Departement Reports in 2013 obtained Puskesmas Kampung Delima has thehighest percentage of 17,67% suffer from Rheumatoid Arthritiswith the largest group inthe elderly. The aim of research identified the influence of tai-chi exercise to the intensityof the pain of Rheumatoid Arthritis in the elderly. This study was pre experiment, withdesign one group pretest-posttest. The total sample was 35 respondents, taken bypurposive sampling. The reseach result was efffect of tai-chi exercise in reducing painintensity Rheumatoid Arthritis in the elderly. Tai-chi exercise was recommended to usethe elderly in order to reduce the intensity of pain Rheumatoid Arthritis.